Endogenous risk-taking and physical appearance of sex workers - Egger, Peter; Lindenblatt, Andreas (The European journal of health economics, 2015)
Previous research found that physical appearance affects the risk-taking of sex workers through offering unprotected services. This paper utilizes a large individual-level data set covering 16,583 pay-for-sex contracts in 2011 and 2012 by 2,517 female suppliers in Germany. Results based on instrumental variables suggest that the incentive for risk-taking is about twice as high than when assuming random assignment of risk-taking.
Published online: 21 October 2014
Gesehen am 09.07.2020